The Role of Parents in Their Children’s Artistic Education: The Effect of Parental Involvement in the Transgenerational Process - Szűcs, Tímea; Váradi, Judit; Kelemen, Henrietta; Miklódi-Simon, Zsófia; Pusztai, Gabriella (Harmonia: Journal of Arts Research and Education, 2023)
Little is known about the methods and effects of parental involvement in art education. The aim of our systematic literature review is to explore the types of parental involvement in four branches of art (music, dance, visual arts, and theatre). We conducted our research with the help of the EBSCO database, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedure. We found that the share of the different artistic fields is highly disproportionate in the literature on parental involvement. Compared to music, theatre, dance, and visual arts, coverage is negligible. During our study, we managed to classify types of parental involvement and found that it showed variety across different branches of art.